The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201501116
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Construction of Heteroatom‐Containing π‐Conjugated Systems by Intramolecular Oxidative CH/CH Coupling Reaction

Abstract: Synthesis of heteroatom-containing ladder-type π-conjugated molecules was successfully achieved via a palladium-catalyzed intramolecular oxidative C-H/C-H cross-coupling reaction. This reaction provides a variety of π-conjugated molecules bearing heteroatoms, such as nitrogen, oxygen, phosphorus, and sulfur atoms, and a carbonyl group. The π-conjugated molecules were synthesized efficiently, even in gram scale, and larger π-conjugated molecules were also obtained by a double C-H/C-H cross-coupling reaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 71 publications
1
56
0
Order By: Relevance
“…In recent years, it was shown that some nonconjugated polymers containing amine group such as poly(amidoamine) showed excellent fluorescent emission . Further studies exhibited that the heteroatom‐containing double bonds in these nonconjugated polymers may contribute to their excellent photoluminescent performance . The detailed fluorescent mechanism of amine‐contained nonconjugated polymers is still under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it was shown that some nonconjugated polymers containing amine group such as poly(amidoamine) showed excellent fluorescent emission . Further studies exhibited that the heteroatom‐containing double bonds in these nonconjugated polymers may contribute to their excellent photoluminescent performance . The detailed fluorescent mechanism of amine‐contained nonconjugated polymers is still under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, incomplete conversion of the starting reagents 3 and 4 into target products 5 was observed even after long reaction times (up to 2 weeks). In all cases, the starting reagent 3a-g was partially recovered after the reaction was stopped (see Table 1, entries [8][9][10][11][12][13][14][15]. Mercury 25 representation of the X-ray crystal structure of 5a with thermal ellipsoids of 50% probability.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10] Palladium-catalyzed C-H intermolecular and/or intramolecular arylation offers one of the most efficient and reliable methods for the construction of different polycyclic structures. [11][12][13][14][15] In this communication, we present a new and simple route to dithienoquinazoline and benzo [f]thieno [3,2-h]quinazoline systems I-III, based on Pd-catalyzed intramolecular cyclization, proceeding under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy for the synthesis of heteroatom containing π conjugated molecules is C H/C H coupling reaction of heteroatom bridged biaryl compounds (Scheme 19). 31,32 This reaction provided a variety of π conjugated molecules bearing heteroatoms, such as nitrogen, oxygen, phosphorus, and sulfur atoms, and in some cases also a carbonyl group. The π conjugated molecules were synthesized ef ciently, even on a gram scale, and larger π conjugated mole cules could also be obtained by a double C H/C H cross coupling reaction and subsequent oxidative cycloaromatization (Scheme 19, bottom row).…”
Section: H Transformations Leading To the Synthesis Of Organic Funcmentioning
confidence: 99%